Instructivo para pruebas a interruptores de potencia en subestaciones eléctricas soportado en plataforma virtual (2020)
The purpose of this comprehensive degree work is to design the instructions for testing power switches in electrical substations supported on a virtual platform with the protocols, procedures, and analysis on how the necessary tests should be carried out on power switches and information from other equipment. patio in electrical substations, in accordance with International, National standards and recommendations given by the manufacturer. As a study and training for the users of this manual, information is presented on transformers, switches, overcurrent relays related to the components that make them up, how they work and the different types that exist in the market. The steps to follow during the process are specified, as well as how they should be carried out and what equipment is appropriate to carry out this type of tests. Likewise, the different tests that must be carried out according to the protocol of electrical substations are presented, based on the RETIE (Technical Regulation of electrical installations) regulations. This instructive is preceded by instructions for safety regulations, equipment and tools used and finally the manual is reflected in a virtual platform implemented with free software AUTOPLAY: With access to this platform, students of engineering and industrial electromechanical maintenance technology can perform theoretical training to acquire the necessary skills to carry out this type of work in an electrical substation.